The Price of Progress: Unpacking the Cost of AI Medical Imaging Software - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Price of Progress: Unpacking the Cost of AI Medical Imaging Software The integration of Artificial Intelligence (AI) into medical imaging—from radio...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Medical Imaging